Mechanical Properties of PVA/Alginate Membranes Fabricated using Electrospinning as A Wound Dressing - Putri Endah Puspita Sari; Ngurah Ayu Ketut Umiati; A Subagio (Department of Physics, Sebelas Maret University, 2024)
Alginate is an interesting natural biopolymer due to its many benefits and good biological properties. Observing the mechanical properties of PVA/Alginate fibers made by electrospinning machines can help predict their behavior and measure their performance under various conditions including applied external forces. Therefore, this study investigated the elastic properties of PVA/Alginate membranes, specifically tensile strength and elongation. The fabrication material used is PVA / Alginate solution with a PVA solution concentration of 20% and alginate solution 2.5%. The electrospinning process is carried out by optimizing at a voltage of 25 kV, the distance between the spinneret end and the collector is 15 cm, the flow rate is 130, and the spinneret diameter variations are 0.4 mm, 0.6 mm, and 0.8 mm. To determine the morphology of the fiber surface, observations were made using ocular microscopes and SEM. From this observation, it is known that the morphology formed using a 0.4 mm spinneret has the tightest structure among the three sizes of spinneret diameter. To determine the effect of spinneret diameter on the value of tensile strength and elongation, tensile strength tests are carried out. The tensile strength and elongation values of the membrane obtained with variations in spinneret diameters of 0.4 mm, 0.6 mm, and 0.8 mm are 1.96 MPa, 3.77 MPa and 6.11 MPa respectively and the elongation values are 17%, 52.7%, and 97%. With medical material standards, it has a tensile strength value between 1 MPa – 24 MPa and an elongation value between 17% – 207%, so that PVA / Alginate fiber membranes have the potential to be applied as wound dressings.